Measuring the impact of monoclonal antibody therapies - Lim, Ka Keat; Ng, Kenrick; Balachandran, Sathiyaa; Russell, Mark D.; Boalch, Amy; Sinclair, Alasdair; Coker, Bolaji; Vinnakota, Krishna; Mansoor, Rashid; Douiri, Abdel; Marks, Lara V.; Sacks, Steven (Frontiers in Medicine, 2023)
Monoclonal antibody (Mab) treatments have significantly improved the quality and quantity of life, but are some of the most expensive treatments, resulting in some hesitance to introduce new Mab agents. A system for estimating the impact of Mab drugs in general would optimally inform health strategy and fully realise how a single scientific discovery can deliver health benefits. We evaluated such a method with several well-established Mab regimens.We selected five different Mab regimens in oncology and rheumatology in England. We carried out two systematic literature reviews and meta-analyses to assess health outcomes (Health assessment questionnaire-disability index for rheumatoid arthritis; overall mortality for melanoma) from realworld data, compared to the outcomes from randomised control trials (RCTs). We applied economic modelling to estimate the net monetary benefits for health outcomes for estimated patient population size for each Mab regimen.Meta-analyses of 27 eligible real-world data (RWD) sets and 26 randomised controlled trial (RCT) sets found close agreement between observed and expected health outcomes. A Markov model showed net positive monetary benefit in three Mab regimens and negative benefit in two regimens. However, because of limited access to NHS data, the economic model made several assumptions about the number of treated patients and the cost of treatment to the NHS, the accuracy of which may affect the estimation of net monetary benefit.RCT results reliably inform the real-world experience of Mab treatments. Calculation of net monetary benefit by the algorithm described provides a valuable overall measure of health impact, subject to the accuracy of data inputs. This study provides a compelling case for building a comprehensive, systematised, and accessible database, and related analytics, on all Mab treatments within health services.